2020
DOI: 10.1186/s12885-020-06803-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor efficacy in colon cancer using EGF functionalized PLGA nanoparticles loaded with 5-Fluorouracil and perfluorocarbon

Abstract: Background: Tumor recurrence and metastasis occur at a high rate in patients with colon cancer. Identification of effective strategies for the treatment of colon cancer is critical. Recently, poly (lactic-co-glycolic acid) (PLGA) has been shown to have potential as a broad therapeutic drug delivery system. We designed a dual-loaded nanoparticle drug delivery system to overcome the limitations of chemotherapeutic drugs used to treat colon cancer. Methods: We developed epidermal growth factor (EGF) functionalize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 29 publications
(29 reference statements)
0
25
0
Order By: Relevance
“…PLGA copolymers were approved by the FDA for numerous applications, including controlled-release NPs for colon targeting. 17 It has been proven that the time required for the degradation of PLGA is associated to the ratio of monomers used in its production, ie, controlling the degradation rate can be achieved by adjusting the ratio of DL-lactide to glycolide in the copolymer. 18 EL30D55 and ES100 are proven to be biocompatible enteric polymers for oral formulations.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA copolymers were approved by the FDA for numerous applications, including controlled-release NPs for colon targeting. 17 It has been proven that the time required for the degradation of PLGA is associated to the ratio of monomers used in its production, ie, controlling the degradation rate can be achieved by adjusting the ratio of DL-lactide to glycolide in the copolymer. 18 EL30D55 and ES100 are proven to be biocompatible enteric polymers for oral formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the antitumor effects of 5FU could be improved including proliferation suppression and apoptosis [ 40 ]. An in vitro study showed there was a burst release of 17.22% of FU at 7 h and furthermore, there was a controlled release up to 78.23% for 24 h. The nanoparticles exhibited a biphasic drug release pattern with initial accelerated release followed by sustained release over seven days [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of perfluorocarbon as an artificial oxygen carrier to improve tumor oxygenation could act synergistically with 5-FU delivery, enhancing its cytotoxic effects. Indeed, perfluorocarbon presented an additive antitumor effect for 5-FU, as the most drastic in vivo antitumor effect was observed in the case of EGF-PLGA-5-FU-PFC administration [ 181 ].…”
Section: Organic Nanosized Drug-delivery Systems For Crc Therapymentioning
confidence: 99%